2014
DOI: 10.1088/0264-9381/32/1/015024
|View full text |Cite
|
Sign up to set email alerts
|

Generalized quadratic curvature, non-local infrared modifications of gravity and Newtonian potentials

Abstract: Metric theories of gravity are studied, beginning with a general action that is quadratic in curvature and allows arbitrary inverse powers of the d'Alembertian operator, resulting in infrared non-local extensions of general relativity. The field equations are derived in full generality and their consistency is checked by verifying the Bianchi identities. The weak-field limit is computed and a straightforward algorithm is presented to infer the post-Newtonian corrections directly from the action. This is then a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 85 publications
4
85
2
Order By: Relevance
“…(6) the "RR" model. Further work on the RR and RT models has been presented in [51][52][53][54][55][56][57][58][59].…”
Section: An Overview Of Nonlocal Modelsmentioning
confidence: 99%
“…(6) the "RR" model. Further work on the RR and RT models has been presented in [51][52][53][54][55][56][57][58][59].…”
Section: An Overview Of Nonlocal Modelsmentioning
confidence: 99%
“…The other possibility for constructing transverse equations of motion, considered for instance in [65,75,96,104], is to start with a generally-covariant (formal) action. Indeed, say we have such an action for pure gravity…”
Section: Action-based Modelsmentioning
confidence: 99%
“…Therefore, gravity becomes unstable as soon asM 2 eff < 0. The Maggiore and Maggiore -Mancarella models, which correspond to the case ξ = 0, are currently receiving particular attention [71,76,78,104,119] because their phenomenology seems to privilege them among other non-local models that have been confronted with observations [65,68,70,73,74,97,107,109,110,[120][121][122][123][124]. Indeed, they have recently passed the constraints of a full Boltzmann/Monte Carlo Markov Chain analysis [78], of which they come out as statistically indistinguishable from ΛCDM, with respect to the current precision of the data.…”
Section: The Potentially Viable Modelsmentioning
confidence: 99%
“…The integral dependence of the corrections could generate the observed acceleration at the present cosmological epoch dynamically and without special fine-tunings. However, detailed investigations have shown that, although the function f can be chosen in such a way that the background expansion is consistent with the data [21][22][23] and the model has a viable Newtonian limit [24,25], the impact of the nonlocal corrections on the evolution of perturbations is strong and utterly rules the model out when this is confronted with large-scale structure data [26]. On top of that, nonlocal modifications of gravity result generically in instabilities at the level of perturbations, at least if they involve tensorial terms such as (W µνρσ / 2 )W µνρσ [27] with W µνρσ the Weyl tensor appearing in models inspired by the conformal anomaly [28,29].…”
Section: Introductionmentioning
confidence: 99%